Quantitative determination of tannin content in medicinal plants - Kuznietsova, Olena (Problems of Environmental Biotechnology, 2021)
The group of tannins includes substances of plant origin, which are complex organic compounds that are derivatives of polyatomic phenols with a variety of chemical structures. There are a lot of methods for quantitative determination of tannins content such as gravitometric methods, permanganatometric titration, spectrophotometric and high performance liquid chromatography methods. In the work, the comparative analysis of these methods was carried out.